2015
DOI: 10.1007/s00165-014-0300-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and enhancement of the IEEE 802.11 RTS/CTS scheme in an error-prone channel

Abstract: In this paper, we present a new discrete time Markov chain model to estimate the packet transmission probability τ, in order to develop mathematical models to derive the saturation throughput and the average packet delay of a 802.11 wireless LAN based on the RTS/CTS access method in the presence of noise, which distorts transmitted frames. Besides the standard backoff rule of the 802.11, Distributed Coordination Function assumes that each loss in the network is caused only by collision and acts to treat this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…By analyzing the signal strength of nodes in a 3D simulation environment, they concluded that the proposed scheme has effective throughput performance compared with that of the standard model. The authors of [25] improved the conventional RTS/CTS scheme proposed for IEEE 802.11 in order to classify why some transmission fail. According to the proposed model, the packets are immediately transmitted after failure due to noise.…”
Section: Rts/cts Scheme For Previous Standardsmentioning
confidence: 99%
“…By analyzing the signal strength of nodes in a 3D simulation environment, they concluded that the proposed scheme has effective throughput performance compared with that of the standard model. The authors of [25] improved the conventional RTS/CTS scheme proposed for IEEE 802.11 in order to classify why some transmission fail. According to the proposed model, the packets are immediately transmitted after failure due to noise.…”
Section: Rts/cts Scheme For Previous Standardsmentioning
confidence: 99%
“…However, they were a solid starting point for further research. Most of all, they resolved the complicated problem of representing multiple states of the channel access procedure by using Markov chains (see Kosek-Szott et al, 2011;Yazid et al, 2014aYazid et al, , 2014bYazid et al, , 2015b. In this area, Kong et al (2004) presented an analytical model of the IEEE 802.11e EDCA taking into account AIFS and CW.…”
Section: Introductionmentioning
confidence: 99%